PENGARUH JENIS DAN DOSIS PENGAPURAN TERHADAP PERTUMBUHAN TANAMAN NILAM (Pogostemon cablin BENTH.) PADA TANAH GAMBUT - Wira Hadianto; Yusrizal Yusrizal; Deni Yuwanda (Universitas Teuku Umar, 2020)
Patchouli (Pogostemon cablin Benth.) Is one of the essential oil producing plants of the Labiatae family. This study aims to determine the type and dosage of liming on the growth of patchouli on peat soils. And whether these two factors are real or not. Some of the ingredients used as ameliorant are shell ash, eggshell, and dolomite. This research was conducted in the experimental garden of the Faculty of Agriculture, Teuku Umar University, Meulaboh, Aceh Barat on 29 October 2019 to 13 February 2020. This study used a 3 x 3 factorial randomizedblock design with 3 replicates. Variables observed included changes in soil pH at 7 and 90 HSA, number of shoots and number of leaves at 15, 30 and 45 HST, plant height and number of branches at 60, 75 and 90 HST and leaf wet and dry weight at 90 HST. The results showed that the administration of liming species was able to influence the parameters of soil pH changes at 7 and 90 HSA, the number of leaves aged 45 HST, and the number of branches aged 90 HST and the best treatment was found on the shells of shells. The administration of liming dose is able to influence the parameters of soil pH changes at 7 HSA, plant height aged 60, 75 and 90 HST, number of branches aged 60 HST and the best treatment is found at a dose of 31.25 grams / polybag. Provision of liming type and dosage gives an interaction effect on soil pH changes at 7 HSA and the number of branches aged 60, 75 and 90 HST and the best treatment is found in clam shells with a dose of 31.25 grams / polybag.Keywords: Patchouli, Calcification, Peatland